Vitamin C and Coronavirus Disease 2019: A review of the literature - Flores-Silva, Carlos Humberto (2021)
Introduction. The pandemic by the coronavirus disease 2019 (COVID-19) has generated a global sanitary crisis and dispite the elapsed time there is still no medicament that has been shown to prevent or cure it, especially in the most grave cases. Some investigators have proposed the use of vitamin C, due to its imnunoregulatory and antioxidant effects, as a preventive measure or adjuvant therapy against the pandemic. Because of this, the present review of the literatue has been made to determine the feasibility of these effects and if there is scientific evidence that supports its use as a preventive or adjuvant therapeutic against COVID-19.